Taxing the Establishment Clause: Revolutionary Decision of the Arizona Supreme Court - Kevin G. Welner (Arizona State University, 2000)
This article explores the nature and implications of a 1999 decision of the Arizona Supreme Court, upholding the constitutionality of a state tax credit statute. The statute offers a $500 tax credit to taxpayers who donate money to non-profit organizations which, in turn, donate the money in grants to students in order to help defray the costs of attending private and parochial schools. The author concludes that the Arizona decision elevates cleverness in devising a statutory scheme above the substance of long-established constitutional doctrine.